Broadband, efficient extraction of quantum light by a photonic device comprised of a metallic nano-ring and a gold back reflector - Haws, Cori; Perez, Edgar; Davanco, Marcelo; Song, Jin Dong; Srinivasan, Kartik; Sapienza, Luca (American Institute of Physics, 2022)
To implement quantum light sources based on quantum emitters in applications, it is desirable to improve the extraction efficiency of single photons. In particular, controlling the directionality and solid angle of the emission are key parameters, for instance, to couple single photons into optical fibers and send the information encoded in quantum light over long distances, for quantum communication applications. In addition, fundamental studies of the radiative behavior of quantum emitters, including studies of coherence and blinking, benefit from such improved photon collection. Quantum dots grown via Stranski？Krastanov technique have shown to be good candidates for bright, coherent, indistinguishable quantum light emission. However, one of the challenges associated with these quantum light sources arises from the fact that the emission wavelengths can vary from one emitter to the other. To this end, broadband light extractors that do not rely on high-quality factor optical cavities would be desirable, so that no tuning between the quantum dot emission wavelength and the resonator used to increase the light extraction is needed. Here, we show that metallic nano-rings combined with gold back reflectors increase the collection efficiency of single photons, and we study the statistics of this effect when quantum dots are spatially randomly distributed within the nano-rings. We show an average increase in the brightness of about a factor 7.5, when comparing emitters within and outside the nano-rings, in devices with a gold back reflector, and we measure count rates exceeding 7？×？10 6 photons per second and single photon purities as high as 85% ± 1%. These results are important steps toward the realization of scalable, broadband, easy to fabricate sources of quantum light for quantum communication applications.